Improving the Quality of Single-Phase Grid-Connected Solar Systems Using Iterative Control Method - Mazharul Islam; Sadia Afrin; Suraia Akter Rakhi (Advances in Engineering and Intelligence Systems)
Voltage source inverters (VSIs) are the most common type of inverter used in power electronic systems for distributed generation sources. In three-phase systems, using three-phase conversion to the synchronous reference frame, linear controllers can be easily used to control the inverter due to the conversion of AC parameters in the synchronous frame to dc components. The design of linear controllers in single-phase systems is often difficult because of the oscillating nature of these systems. In some cases, single-phase conversion to synchronous frame is used, which has its problems, such as delays in converting single-phase values to two-phase. To tackle this problem, proportional-resonance (PR) instruments can be used at a specific resonant frequency. However, for single-phase systems where all the harmonies are present in the inverter current, an unlimited number of PR instruments are required. Therefore, not all harmonies can be controlled in this way. To overcome this, a iterative control system can be used. The control method presented in this paper uses delay intervals with positive feedback. Under these conditions, the control gain in the dynamic model of the iterative control system is very high for all harmonies and allows tracking the reference current and voltage values with a zero steady-state error in all harmonies. In addition, the performance of the iterative control system in the face of single-phase systems will be very favorable.